2011
DOI: 10.1007/s00005-011-0154-x
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholines: Bioactive Lipids Generated During Storage of Blood Components

Abstract: Transfusion-related acute lung injury (TRALI) is suggested to be a "two hit" event, resulting from priming and activation of pulmonary neutrophils. It is known that neutrophil activation may result from infusion of lysophosphatidylcholines (LysoPCs) accumulated during storage of blood components. The aim of our study was to verify whether the LysoPCs are released into the storage medium of blood components. We measured the LysoPCs concentration in the supernatants from stored apheresis platelet concentrates (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…In these models LPS was also used as "first hit" followed by either aged RBCs or aged PLTs. LysoPCs did not accumulate in both murine and human aged RBCs and were only slightly elevated in aged PLTs [47,48] which was also confirmed by two other groups [54,55]. Clinical studies also report conflicting results on the role of lysoPCs [56,57].…”
Section: Bioactive Lipidssupporting
confidence: 56%
See 3 more Smart Citations
“…In these models LPS was also used as "first hit" followed by either aged RBCs or aged PLTs. LysoPCs did not accumulate in both murine and human aged RBCs and were only slightly elevated in aged PLTs [47,48] which was also confirmed by two other groups [54,55]. Clinical studies also report conflicting results on the role of lysoPCs [56,57].…”
Section: Bioactive Lipidssupporting
confidence: 56%
“…Moreover, in vitro priming studies showed that accumulation of LysoPCs is not cell derived, but plasma derived and storage temperature dependent as opposed to storage time related. Neutrophil priming in these reports was LysoPCs independent [54,57]. These different results are possibly explained by different storage procedures.…”
Section: Studymentioning
confidence: 67%
See 2 more Smart Citations
“…-non-immune-mediated TRALI, which may be attributed to transfusion of biologically active compounds accumulated in stored blood components such as bioactive lipids, proinfl ammatory cytokines or platelet microparticles with high procoagulant activity. A high potassium level is considered an additional risk factor [4,[13][14][15][16][17][18][19][20]. Leukocyte antibodies are currently believed to be crucial for TRALI development.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%